Response of varying levels of phyto-hormones and micro-nutrients on growth and yield of brinjal (Solanum melongena L.) in sub-tropical Terai region of India - Bhattarai, Basant Raj; Pal, Akhilesh Kumar; Amgain, Lal Prasad (Journal of Agriculture and Natural Resources, 2021)
A field study was conducted at Horticultural Research Farm, Institute of Agricultural Sciences of Banaras Hindu University, Varanasi, India during summer season of 2017-2018 to test the sole effect of phyto-hormones and micro-nutrients on growth of brinjal (Solanum melongena, L.). The thirteen treatments having six different concentration of phytohoromnes viz., T1 (20 ppm NAA), T2 (40 NAA), T3 (60 ppm NAA), T4 (25 ppm GA3), T5 (50 ppm GA3), T6 (75 ppm GA3), and six different concentrations of micronutrients viz., T7 (Boron 0.1%),T8 (Boron 0.2%), T9 (Boron 0.3%), T10 (Zinc 0.1%), T11 (Zinc 0.2%), T12 (Zinc 0.3%) and T13 (control-water spray) for a “Kashi Uttam” cultivar of brinjal were grown under randomized complete block design (RCBD) having three replications. The results findings indicated that treatment T4 (25 ppm GA3) had significant effect on growth parameters, mainly plant height, number of leaves, leaf length, leaf width, crop canopy, number of side roots and main root length. Similarly, yield parameters like number of fruits per plant, fruit weight, fruit yield per plant were found to be significantly superior under treatment T4 (25 ppm GA3). Number of branches per plant, stem diameter, main root length and fruit weight were found superior under treatment T1 (20 ppm NAA). Among the different concentrations of micronutrients treatment T9 (Boron 0.3%) and T12 (Zinc 0.3%) were found to be significant over control. It can be concluded that the phyto-hormones and micro-nutrients can be judiciously used for increasing the growth and yield of brinjal.